Optimizing the efficiency of a three-step fed anoxic/aerobic sequencing batch reactor using response surface methodology - Gurtekin, Engin (Wiley, 2023)
In this study, the removal of chemical oxygen demand (COD), ammonium nitrogen (NH4+-N) and total inorganic nitrogen (TIN) in a three-step fed anoxic/aerobic sequencing batch reactor was investigated. Response surface methodology (RSM) was used to determine and optimize the effect of operating parameters such as the ratio of aerobic/anoxic (Ae/Ax) phase durations, percentage of feeding to the first anoxic phase (R1) and ratio of feeding percentages to the third and second anoxic phases (R3:R2). The results of the analysis of variance (ANOVA) showed that the three independent variables were statistically highly significant (p < 0.0001). The values of the determination coefficient (R-2) for the removal efficiency of COD, NH4+-N and TIN was 0.9558, 0.9334 and 0.9963, respectively, indicating a good agreement between the experimental results and the predicted values. The quadratic model was valid in predicting experimental results. The optimum conditions obtained using the desirability function were found to be 2.05 for the ratio of Ae/Ax phase durations, 43.09% for R1 and 0.86 for R3:R2, where the COD, NH4+-N and TIN removal efficiency was 94.29, 97.83 and 86.86%, respectively. As a result of the evaluation of the interactive effect of the independent variables, it was determined that R1 was the most effective factor. The results showed that RSM could be used for optimization of operating parameters and improvement of efficiency in a three-step fed anoxic/aerobic sequencing batch reactor.
Keywords: central composite design; nitrification; process optimization; sequencing batch reactor